2012
DOI: 10.1094/mpmi-06-11-0165
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-Responsive Element-Binding Factor 5, ERF5, Is Involved in Chitin-Induced Innate Immunity Response

Abstract: Our recent work demonstrated that chitin treatment modulated the expression of 118 transcription factor (TF) genes in Arabidopsis. To investigate the potential roles of these TF in chitin signaling and plant defense, we initiated an interaction study among these TF proteins, as well as two chitin-activated mitogen-activated protein kinases (MPK3 and MPK6), using a yeast two-hybrid system. This study revealed interactions among the following proteins: three ethylene-responsive element-binding factors (ERF), fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 73 publications
7
130
3
Order By: Relevance
“…We suggest that ERF5 is a mediator of CAPE1 defense responses because of the GCC box, a cis-acting element found in the promoter of many JA/ethylene-inducible and PR genes. ERF5 was also demonstrated to positively regulate SA signaling and plant immunities against the bacterial pathogen Pst DC3000 and improve plant resistance to pathogens by activating several PR genes (Moffat et al, 2012;Son et al, 2012). In tomato, the overexpression of ERF5 was observed to induce PR genes and conferred tolerance to Ralstonia solanacearum (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…We suggest that ERF5 is a mediator of CAPE1 defense responses because of the GCC box, a cis-acting element found in the promoter of many JA/ethylene-inducible and PR genes. ERF5 was also demonstrated to positively regulate SA signaling and plant immunities against the bacterial pathogen Pst DC3000 and improve plant resistance to pathogens by activating several PR genes (Moffat et al, 2012;Son et al, 2012). In tomato, the overexpression of ERF5 was observed to induce PR genes and conferred tolerance to Ralstonia solanacearum (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Expression of several of these, including ERF1, ERF5, ERF6, RAP2.2, and ORA59, influences host susceptibility to B. cinerea, with ERF5 a key component of chitinmediated immunity (Berrocal-Lobo et al, 2002;Pré et al, 2008;Moffat et al, 2012;Son et al, 2012;Zhao et al, 2012). Members of the MYB and NAC families (Wang et al, 2009;Ramírez et al, 2011a) have also been shown to influence plant susceptibility to B. cinerea.…”
Section: Introductionmentioning
confidence: 99%
“…These contain an N-terminally located conserved stretch of acidic amino acids (called the 2nd Conserved Motif of group IX [CMIX-2]), which might function as a transcriptional activator domain. The transcriptional activators ERF5 and ERF6 additionally harbor a conserved C-terminal motif (CMIX-5) identified as a putative phosphorylation site by mitogen-activated protein kinases (MPKs), which distinguishes group IXa from group IXb (Fujimoto et al, 2000;Nakano et al, 2006).ERF6 is an activating transcription factor with documented roles in the response to various abiotic and biotic stress conditions, such as oxidative stress (Sewelam et al, 2013;Wang et al, 2013;Vermeirssen et al, 2014), high light (Vogel et al, 2014), cold (Lee et al, 2005;Xin et al, 2007), and biotic stress induced by biotrophic and necrotrophic pathogens (AbuQamar et al, 2006;Dombrecht et al, 2007;Hu et al, 2008;Moffat et al, 2012;Son et al, 2012;Meng et al, 2013). We have previously unraveled the molecular and biological function of ERF6 and its close homolog ERF5 in the mannitol-induced stress response, specifically in actively growing young Arabidopsis leaves (Dubois et al, 2013).…”
mentioning
confidence: 99%